Disposition kinetics of diclofenac in the dual perfused rat liver. Issue 9 (23rd April 2013) - Sahin, Selma; Rowland, Malcolm; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract This study investigates the hepatic disposition of diclofenac as a function of route of input: portal vein (PV) versus hepatic artery (HA) in the presence of its binding protein, albumin. The in situ dual perfused rat liver was performed using Krebs bicarbonate buffer containing human serum albumin (HSA, 0.25%–1%) at constant PV (12 mL/min) and HA (3 mL/min) flow rates. Bolus doses of [14C]–diclofenac and 125I‐labeled HSA were injected randomly into the HA or PV and then, after an appropriate interval, into the alternate vessel. Regardless of route of input and perfusion medium protein concentration, the hepatic outflow profile of diclofenac displayed a characteristic sharp peak followed by a slower eluting tail, indicating that its radial distribution is not instantaneous. Based on the estimated effective permeability‐surface area product/blood flow ratio, hepatic uptake of diclofenac is governed by both perfusion and permeability. Fractional effluent recovery (F) increased as unbound diclofenac fraction in the perfusate decreased. Although no significant difference in hepatic clearance of diclofenac as a function of route of delivery at 0.5% and 1% HSA, it was demonstrable at 0.25% HSA (p < 0.001), when the extraction ratio is higher. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3220–3227, 2013